2015
DOI: 10.1530/rep-14-0410
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of porcine partially reprogrammed iPSCs from adipose-derived stem cells

Abstract: Partially reprogrammed induced pluripotent stem cells (PiPSCs) have great potential for investigating reprogramming mechanisms and represent an alternative potential material for making genetically modified animals and regenerative medicine. To date, PiPSCs have scarcely been reported in detail when compared with mice and humans. In this study, we obtained PiPSCs from porcine adipose-derived stem cells (pADSCs) by ectopic expression of human transcription factors (OCT4, SOX2, c-MYC, and KLF4) in feeder-free co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Compared with pre-iPSC lines, several common characteristics, such as incomplete expression of pluripotent genes, inactive X chromosomes in female cells, and inability to generate germline chimeras, have been observed [ 10 , 20 , 21 , 32 ]. In porcine studies, the majority of pig iPSC lines were partially reprogrammed, showing dependence on transgenes, lack of NANOG expression, failure of epigenetic reprogramming, and inability to form chimeras [ 22 27 ]. According to previous studies, the majority of piPSC lines exhibited dependency of continuous transgene expression, and it was impossible to obtain transgene-independent colonies using a transgene-free system such as drug-inducible, episomal or plasmid vectors [ 23 , 26 , 39 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with pre-iPSC lines, several common characteristics, such as incomplete expression of pluripotent genes, inactive X chromosomes in female cells, and inability to generate germline chimeras, have been observed [ 10 , 20 , 21 , 32 ]. In porcine studies, the majority of pig iPSC lines were partially reprogrammed, showing dependence on transgenes, lack of NANOG expression, failure of epigenetic reprogramming, and inability to form chimeras [ 22 27 ]. According to previous studies, the majority of piPSC lines exhibited dependency of continuous transgene expression, and it was impossible to obtain transgene-independent colonies using a transgene-free system such as drug-inducible, episomal or plasmid vectors [ 23 , 26 , 39 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human as a non-permissive species, NANOG plays an important role in reprogramming and maintaining pluripotency [ 56 , 57 ]. In some pig studies, NANOG upregulation and epigenetic reprogramming were not achieved [ 26 , 27 ]. Consistent with previous studies, we confirmed that generated iPSCs carrying whole Yamanaka’s factors have no NANOG expression, and that epigenetic alteration relied on the expression of transgenes for maintenance (Figs 3C and 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, biPSCs exhibiting packed dome morphology Because of their multipotent nature, capacity for self-renewal, easy collection, and amplification in vitro, ASCs have become an ideal candidate for regenerative medicine, and donor cells in SCNT and iPSCs research (Abouhamzeh et al, 2015;Ren et al, 2014;Wei et al, 2015;Y. Zhang et al, 2014).…”
Section: Hypoxia Promotes Reprogramming Of Bascs Into Ipscsmentioning
confidence: 99%
“…Donor cells were prepared as previously described (Wei et al 2015). Briefly, cells of passages 3-7 were trypsinized and re-suspended in TCM199 supplemented with 2% FBS.…”
Section: Scnt Process and Culturementioning
confidence: 99%